Research Data Processing Through Structural Equation Model-Partial Least Square (SEM-PLS) Method - Petrolis Nusa Perdana; Diah Armeliza; Hera Khairunnisa; Hafifah Nasution (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
Structural Equation Modeling (SEM) is one type of multivariate analysis in the social sciences. Multivariate analysis is the application of statistical methods to analyze several research variables simultaneously. This community service activity was held and aimed at the academic community (lecturers and students) from partner campuses of the Faculty of Economics, State University of Jakarta, they are FEB UHAMKA, STIE Indonesia, and Tempo Polytechnic with the aim of providing knowledge about research methodologies, especially the Structural Equation Modeling method (SEM) – Partial Least Squares (PLS) which has various advantages compared to other PLS software as described above. Another goal is expected to help improve the ability of the partner academic community in making scientific articles to be published in national and international journals. In addition, in this training, partners are also trained for hands-on practice using the Warp PLS Ver Software. 5.0. The method of implementing this community service activity is in the form of a workshop that includes providing material related to the SEM-PLS method as well as direct practice in using the WarpPLS software. During the workshop, the partner academic community was also given time to discuss and ask questions directly with the instructor.